A Closer Look at Organizational Culture in Action 2021
DOI: 10.5772/intechopen.93871
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of the Informal Economy: The Case of Street Trading in Ile-Ife, Nigeria

Abstract: Previously, scholars in Nigeria have argued for and against the continuing existence of street trading activity in cities but no known study had examined how street trading could be developed. This chapter seeks to provide empirical evidence for its characteristics, values and challenges in order to provide insights into how street traders could be supported to make their trading activity more productive and sustainable. Findings showed that the street traders need entrepreneurship education, financial support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…A few street traders acknowledged that sometimes poor parking of cars from their customers do cause traffic but considers that as not being their fault but the drivers' fault. The assertion of the traders refutes the study by scholars like Adedeji et al (2014), Mitullah, (2003 and Olaposi (2021) that showed that street vending activities obstruct traffic flow and reduce the capacity of roads and intersections, leading to increased travel times overcrowding, pedestrian accidents and delays for motorists.…”
Section: Safety and Ease Of Timementioning
confidence: 72%
See 2 more Smart Citations
“…A few street traders acknowledged that sometimes poor parking of cars from their customers do cause traffic but considers that as not being their fault but the drivers' fault. The assertion of the traders refutes the study by scholars like Adedeji et al (2014), Mitullah, (2003 and Olaposi (2021) that showed that street vending activities obstruct traffic flow and reduce the capacity of roads and intersections, leading to increased travel times overcrowding, pedestrian accidents and delays for motorists.…”
Section: Safety and Ease Of Timementioning
confidence: 72%
“…One of the main issues is congestion, which occurs when street vendors occupy sidewalks or other public spaces that are meant for pedestrian use. This can lead to overcrowding, pedestrian accidents, and reduced mobility for people with disabilities or limited mobility (Olaposi, 2021). In addition, street traders may obstruct traffic flow and reduce the capacity of roads and intersections, leading to increased travel times and delays for motorists (Mitullah, 2003).…”
Section: Street Vending: Urban Mobility and Urban Communitymentioning
confidence: 99%
See 1 more Smart Citation